Pursuing moral warfare : ethics in American, British, and Israeli counterinsurgency - Schulzke, Marcus (Georgetown University Press, 2019)
During combat, soldiers make critical split-second choices about matters of life and death dozens of times a day. These individual decisions accumulate to determine the outcome of wars. In this book, Marcus Schulzke examines the theory and practice of how military ethics can guide conduct in counterinsurgency, which are particularly difficult operations because the opponent operates outside of the laws of war. Schulzke surveys the ethical traditions that militaries borrow from; compares ethics in practice in the US Army, British Army and Royal Marines Commandos, and Israel Defense Forces; and draws conclusions that may help militaries refine their approaches in future conflicts. The work is based on interviews with American, British, and Israeli soldiers who were deployed between 2000 and 2012, review of training materials and other official publications, published accounts from combat veterans, and observation of US Army focus groups with active duty soldiers. Examining three distinct national militaries illuminates positives and negatives is different approaches to military ethics. Schulzke makes a convincing argument that while moral warfare is an illusive goal, it is possible to make incremental improvements that can reduce war's destructiveness while improving the success of counterinsurgency operations.